Tree diversity reduced soil erosion by affecting tree canopy and biological soil crust development in a subtropical forest experiment - Song, Zhengshan; Seitz, Steffen; Li, Jian; Goebes, Philipp; Schmidt, Karsten; Kühn, Peter; Shi, Xuezheng; Scholten, Thomas (Forest ecology and management, 2019)
•Annual soil erosion rates decreased with tree species richness.•Tree diversity reduced soil erosion by affecting tree canopy and biological soil crust development.•Restoring species-rich plantations may be beneficial for soil erosion control. Biodiversity plays a crucial role in forest ecosystem sustainability. However, it is unclear how tree diversity and especially the relationship between diversity and ecosystem functioning affect soil erosion. Based on a forest biodiversity and ecosystem functioning experiment established in subtropical China (BEF China), we measured soil erosion at four tree species richness levels (monocultures, 8 tree species, 16 tree species and 24 species stands) during the rainy seasons from 2013 to 2015. The result showed that mean annual soil erosion rates were detected to decrease with tree species richness significantly over the observed three years. Leaf area index (LAI) and biological soil crusts (BSCs) were the two main factors driving soil erosion within tree stands of different species richness. Positive effects of tree species richness on tree canopy structure and BSCs might drive the reduction of soil erosion in the earlier successional stage after afforestation of tree plantations. Therefore, we highlight the important influence of tree species richness on soil erosion control, hydrologic processes and thus sustainable ecology services.